CHALLENGES AND OPPORTUNITIES TOWARDS INDUSTRIAL REVOLUTION 4.0 (IR 4.0) AMONG CONTRACTORS IN MALAYSIA CONSTRUCTION INDUSTRY - Sazarina Mohd Sazali; Anis Rosniza Nizam Akbar; Yusmady Md Junus; Siti Nor Azniza Ahmad Sekak (Jurnal Penyelidikan Sains Sosial, 2022)
Industrial Revolution 4.0 refers to an innovation to introduce a new concept of technologies with various potential advantages. The new concept of technology has been implemented in Malaysia and construction player such as contractor have their own perception towards the implementation. The aim of the study is to analyse the Malaysian contractors’ perception on the future opportunities and challenges of IR 4.0 implementation. Hence, a comprehensive study is carried out with objectives to find out the opportunities and challenges towards the contractor in implementation IR 4.0 in construction industry. The selected respondents were from four grades of contractor in Selangor which are G4, G5, G6 and G7 Contractor. This quantitative approach uses questionnaire based on Likert Scale questionnaire. The data collected from questionnaire survey is processed and analysed by using Statistical Packages for Social Science (SPSS) version 22. The response rate is 14% which is 70 respondents out of 487 contractor G4 until G7 in Selangor. It was found that IR 4.0 in construction industry will be more challenges due to the nature of construction industry that are unpredictable, and the contractor is expected to be more competitive to face the challenges of IR 4.0. Besides, the finding shows that the opportunity of IR 4.0 offers contractors to work faster and be more strategic in planning the work programme of the project. Thus, the challenges and opportunities of IR 4.0 indeed. The results from this research can assist in producing a framework for the adoption of IR 4.0 among contractors for the construction in the future.